ANALISIS KUALITAS ASET SISTEM PERBANKAN INDONESIA TAHUN 2000-2011 - Andi Ruslan (Institut Agama Islam Negeri Bone, 2020)
AbstractThe purpose of this study was to determine the quality of the assets or the assets held by the banking system in Indonesia in 2000-2011 by looking at the ratio APYD compared to total earning assets and earning assets (Non-Performing assets) compared to total earning assets owned by commercial banks and Islamic banks in the aggregate ini 2000-2011. The type of data used in this study is secondary data. The data include statistics on Indonesia banking period 2000-2011. Based on the calculations can be seen that the average (mean) ratio APYD Earning Assets, NPA ratio Earning Assets, Earning Asset NPF ratio of commarial banks and Islamic banks over the past ten years each below 5% in the amount of 3.52%, 3.12%, 4.25%. this shows the soundness of the banking Indonesia quality assets performed well.Kata Kunci: Non Performing Assets; Non Performing Financing.